The Influence of Work Motivation on Teacher's Pedagogical Competence - Dewi Wulandari; Endar Nugroho; Mutia Nurul Alifa; Pramesthi Khairunnisa Aulia; Via Aryani (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
A teacher's pedagogical competence is the ability to manage students' learning processes by the applicable foundation. The problem in this study is teacher motivation and pedagogical competence in Limited Face-to-Face Learning activities during the Covid-19 pandemic. This study employs quantitative methods and research instruments such as questionnaires and interviews. This study's sample comprised 46 public junior high school teachers from the Pancoran district in South Jakarta. The sampling technique was carried out using a proportional random sampling technique. According to the study's findings, there is an influence of teachers' work motivation on teachers' pedagogical competence. The teacher's work motivation variable has a 27.0% influence on the teacher's pedagogical competence. Thus, teachers are expected to constantly increase work motivation by maximizing their pedagogic competencies, mainly as face-to-face learning prevails, as before the pandemic. Students' enthusiasm for learning will also rise, resulting in a linear increase in student achievement.